Pemanfaatan Media Pembelajaran Berbasis Game untuk Meningkatkan Hasil Belajar Siswa dalam Mata Pelajaran Ekonomi - Ana Tasya Afani; Mohamad Arief Rafsanjani (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
The low learning outcomes of students in Economics subjects are often influenced by the use of traditional teaching methods that are less engaging and lack interaction. This study aims to examine the effectiveness of utilizing game-based learning media in improving students' academic performance. The game used in this study is the Wordwall game with the Airplane type. A quantitative approach was employed, using a quasi-experimental design with the nonequivalent control group model. The research subjects consisted of two tenth-grade classes at SMA Labschool Unesa 1, with the experimental class receiving treatment using the Airplane game media, while the control class was taught using conventional teaching methods. Data collection was conducted through pre-tests and post-tests. The data were analyzed using normality tests, homogeneity tests, independent t-tests, and N-Gain calculations. The results showed that the implementation of the Airplane game-based learning media significantly improved students' learning outcomes, as indicated by higher average post-test scores and N-Gain values in the experimental group compared to the control group. These findings suggest that game-based media can serve as an innovative alternative in the learning process, as it is capable of enhancing student motivation, active participation, and understanding of economic concepts.